Fatigue and weight loss predict survival on circadian chemotherapy for metastatic colorectal cancer. Issue 14 (30th April 2013) - Innominato, Pasquale F.; Giacchetti, Sylvie; Moreau, Thierry; Bjarnason, Georg A.; Smaaland, Rune; Focan, Christian; Garufi, Carlo; Iacobelli, Stefano; Tampellini, Marco; Tumolo, Salvatore; Carvalho, Carlos; Karaboué, Abdoulaye; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Chemotherapy‐induced neutropenia has been associated with prolonged survival selectively in patients on a conventional schedule (combined 5‐fluorouracil, leucovorin, and oxaliplatin [FOLFOX2]) but not on a chronomodulated schedule of the same drugs administered at specific circadian times (chronoFLO4). The authors hypothesized that the early occurrence of chemotherapy‐induced symptoms correlated with circadian disruption would selectively hinder the efficacy of chronotherapy. METHODS Fatigue and weight loss (FWL) were considered to be associated with circadian disruption based on previous data. Patients with metastatic colorectal cancer (n = 543) from an international phase 3 trial comparing FOLFOX2 with chronoFLO4 were categorized into 4 subgroups according to the occurrence of FWL or other clinically relevant toxicities during the initial 2 courses of chemotherapy. Multivariate Cox models were used to assess the role of toxicity on the time to progression (TTP) and overall survival (OS). RESULTS The proportions of patients in the 4 subgroups were comparable in both treatment arms (P = .77). No toxicity was associated with TTP or OS on FOLFOX2. The median OS on FOLFOX2 ranged from 16.4 (95% confidence limits [CL], 7.2‐25.6 months) to 19.8 months (95% CL, 17.7‐22.0 months) according to toxicity subgroup (P = .45). Conversely, FWL, but no other toxicity, independently predicted for significantly shorter TTP (P < .0001) and OS (P = .001) on chronoFLO4. The median OS on chronoFLO4 was 13.8 months (95% CL, 10.4‐17.2 months) or 21.1 months (95% CL, 19.0‐23.1 months) according to presence or absence of chemotherapy‐induced FWL, respectively. CONCLUSIONS Early onset chemotherapy‐induced FWL was an independent predictor of poor TTP and OS only on chronotherapy. Dynamic monitoring to detect early chemotherapy‐induced circadian disruption could allow the optimization of rapid chronotherapy and concomitant improvements in safety and efficacy. Cancer 2013;119:2564–2573. © 2013 American Cancer Society.